2016
DOI: 10.3748/wjg.v22.i47.10424
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and endoscopic co-operative surgery for non-ampullary duodenal tumors

Abstract: AIMTo assess the safety and feasibility of laparoscopic and endoscopic co-operative surgery (LECS) for early non-ampullary duodenal tumors.METHODSTwelve patients with a non-ampullary duodenal tumor underwent LECS at our hospital. One patient had two mucosal lesions in the duodenum. The indication for this procedure was the presence of duodenal tumors with a low risk for lymph node metastasis. In particular, the tumors included small (less than 10 mm) submucosal tumors (SMT) and epithelial mucosal tumors, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 25 publications
0
49
0
3
Order By: Relevance
“…LECS is an effective backup technique that avoids the risk of delayed perforation after duodenal ESD, but it must be performed in a surgical theatre with the patient under general anesthesia. The recurrence rate after LECS was reportedly 0% [19-21], but only small case series are reported for LECS. Thus, large-scale multicenter studies are needed to clarify the usefulness of the LECS.…”
Section: Characteristics and Treatment Outcome Of Each Er Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LECS is an effective backup technique that avoids the risk of delayed perforation after duodenal ESD, but it must be performed in a surgical theatre with the patient under general anesthesia. The recurrence rate after LECS was reportedly 0% [19-21], but only small case series are reported for LECS. Thus, large-scale multicenter studies are needed to clarify the usefulness of the LECS.…”
Section: Characteristics and Treatment Outcome Of Each Er Methodsmentioning
confidence: 99%
“…LECS, in which the mucosal defect after ESD is closed from the outside of the lumen using laparoscopic suture, was recently implemented for treatment of large SNADETs (≥20 mm) [19-21]. LECS is an effective backup technique that avoids the risk of delayed perforation after duodenal ESD, but it must be performed in a surgical theatre with the patient under general anesthesia.…”
Section: Characteristics and Treatment Outcome Of Each Er Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duodenal stenosis occurred in the case of open conversion but was treated by repeated endoscopic balloon dilatation. ESD: endoscopic submucosal dissection In the literature [10][11][12][13][14][15] , a total seven authors reported a series of LECS for NADENs where the lesions were treated by either ESD and subsequent laparoscopic repair or endoscopy-assisted laparoscopic full-thickness resection and repair without any serious intra-and postoperative complications, corresponding to our results [ Table 3]. In those reports, surgery was occasionally performed for adenocarcinomas confined in the mucosa, but no tumor recurrence was noted in the postoperative course, revealing the feasibility of the indication of LECS for NADENs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent reports demonstrated that LECS offers a promising procedure of choice to facilitate less invasive surgery in the treatment of NADENs [10][11][12][13][14][15] , but the clinical evidence verifying its efficacy remains limited. In this report, we sought to investigate our initial experience of LECS for NADENs and further reveal its clinical significance.…”
Section: Introductionmentioning
confidence: 99%